Penilaian Kinerja dengan Menggunakan Konsep Balanced Scorecard - Rezki Zurriah; Nasrul Kahfi Lubis; Isna Ardila; Nia Agustina (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This study aims to determine and analyze the performance assessment of PT. Bank SumutkcpPulo Brayan which is measured from a financial perspective, customer perspective, internal business process perspective, growth and learning perspective. Sampling in this study is to use a saturated sample selection (simple non random sampling). Data collection techniques in this study were interviews, questionnaires, and literature study, documentacion. The data analysis method used was descriptive qualitative analysis method. The results showed that the assessment of the performance of the PT. Bank SumutKcpPulo Brayan when measured from a financial perspective the results were very bad, the performance assessment of the PT. Bank SumutKcpPulo Brayan when measured from the customer's perspective was good, the performance assessment of the PT. Bank SumutKcpPulo Brayan when measured from the perspective of internal business processes are good, and the performance appraisal of the office of PT. Bank SumutKcpPulo Brayan when measured from a growth and learning perspective is good.